Competence And Performance: The Mediating Role Of Organizational Commitment - Haerul Efendi; Astil Harli Roslan (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
This study aims to analyze the influence of competence on lecturer performance, the influence of competence on organizational commitment, and the influence of organizational commitment on the performance of private university lecturers in Kendari City. This study also examines the role of organizational commitment as a mediating variable in the relationship between competence and performance. The approach used is quantitative with the survey method. The data was collected through a closed questionnaire that was distributed to 230 lecturers of private universities in Kendari City. Data analysis was carried out using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results of the study show that competence has a positive and significant effect on organizational commitment and lecturer performance. Organizational commitment has also been proven to have a positive and significant effect on lecturer performance. In addition, organizational commitment is able to mediate the influence of competence on performance. These findings show that the improvement in lecturers' performance is not only influenced by professional ability, but also by the level of attachment and loyalty to the institution. This research makes a theoretical contribution to the development of a model of competency and performance relationships through organizational commitment, as well as provides practical implications for human resource management in private universities.